Pengaruh Disiplin Kerja dan Budaya Organisasi terhadap Kepuasan Kerja Pegawai pada Dinas Kependudukan dan Catatan Sipil Kabupaten Bima - Ermila; Mawar Hidayanti; Muhammad Yusuf (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Job satisfaction is a crucial factor influencing organizational success, particularly within the delivery of public services. A quantitative approach with an associative design was employed to analyze the effect of work discipline and organizational culture on employee job satisfaction at the Department of Population and Civil Registration, Bima Regency. The sample consisted of 36 civil servants selected through purposive sampling. Data were collected using a Likert-scale questionnaire, tested for validity and reliability, and analyzed through multiple linear regression with the assistance of SPSS version 25. The findings indicate that work discipline does not have a significant effect on job satisfaction, whereas organizational culture shows a positive and significant influence. Simultaneously, both independent variables significantly affect job satisfaction, contributing 18.7% to its variation. These results highlight that strengthening organizational culture plays a more dominant role than disciplinary measures in enhancing employee satisfaction within public institutions.